The impact of different polishing systems on yttria‐stabilized tetragonal zirconia polycrystalline crowns in relation to heat generation - Xiaoyun Liu; John M. Aarts; Sunyoung Ma; Joanne Jung Eun Choi (Wiley, 2023)
Abstract Objectives To investigate the heat generation on yttria‐stabilized tetragonal zirconia polycrystalline (Y‐TZP) crowns during polishing with coarse and fine polishing systems at various speeds. Materials and Methods Two polishers (coarse and fine) at three polishing speeds were investigated. Two simulation models of the first mandibular molars were prepared for full coverage Y‐TZP restorations with different reduction dimensions. Preheated water was pumped into the abutment chamber, to simulate the intrapulpal temperature and blood flow. Twelve Y‐TZP crowns (3M™ Lava™ Esthetic) were milled for each prepared tooth abutment and each cusp (n = 10) was individually ground for 30 s and polished for 2 min. Thermocouple wire was secured to the intaglio surface of the crown and linked to a data logger for recording temperature changes. Selected scanning electron microscopy (SEM) images of the treated surfaces and polishers were analyzed. The data was statistically analyzed using Prism 9. Results The highest temperature rise was observed in the 20,000 RPM polishing speed groups for both coarse and fine polishing, and higher than the threshold value of 5.5°C for pulp damage. The Kruskal-Wallis test, revealed statistically significant differences (p < .0001) in heat generation between low (10,000 RPM) and high (20,000 RPM) polishing speeds. Conclusions High‐speed polishing at 20,000 RPM generated the most heat over the threshold of 5.5°C, which would threaten the dental pulp. The results suggest that a cautionary approach should be taken to high‐speed intraoral polishing. Clinical Relevance Dental clinicians should be aware of the choice of polishing systems and speeds to avoid pulp damage from intraoral polishing of Y‐TZP restorations.